APLIKASI SISTEM INFORMASI PERNIKAHAN (WEDDING INFORMATION SYSTEM) BERBASIS WEBSITE DENGAN METODE FAST - Muhamad Iqbal Wasta Purnama (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The development of information technology continues to grow, this can be an advantage that we can take advantage of, one of which is the use of a Website-Based Wedding Information System Application with the FAST Method. The application is expected to be able to provide marriage information quickly and easily compared to an invitation letter in physical form. Especially during the pandemic because it is difficult to meet face-to-face with many people. The method used is FAST consisting of Scope Definition, Problem Analysis, Requirements Analysis, Logical Design, Physical Design, Construction and Testing using PIECES through questionnaires to 50 participants with the results of Performance 4.44 points, response time and throughput in the very satisfied category, Information 4.48 points from the information provided and presented in the very satisfied category, Economics 4.42 points based on system costs and benefits obtained in the very satisfied category, Efficiency 4.48 points based on the efficiency given to the user in the very satisfied category, Control 4.34 points in the form of system security in the very satisfied category,and Service 4.38 points as the service provided in the very satisfied category.Keywords : Wedding Information System, Wedding, FAST, Website.